Efeito do consumo agudo de erva mate sobre o rendimento fisíco em esteira ergométrica e indicadores metabólicos da exaustão em jogadores profissionais de futebol - Oliveira, Erick Prado de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Background: Yerba mate tea (Ilex Paraguariensis) is an herbal tea beverage consumed mainly in South America that presents components with antioxidant, antinflammatory, and possible ergogenic properties. It is known that exercise increases oxidative stress and muscle damage, and then mate tea intake could show beneficial effects. Purpose: To evaluate the effect of acute intake of yerba mate on blood markers of oxidative stress and muscle damage in female soccer players exposed to exhaustive exercise. Methods: 15 female soccer players (22.1 ± 4.2 years old) were studied randomized with either 5g of soluble yerba mate (400 ml) or 400 ml of water cross-overly with 7 days of washout. Both liquids were given after an overnight fasting and before 60 minutes of a treadmill incremental test up to exhaustion. All subjects were fed with 30g of maltodextrin 30 minutes before the beginning of the test. From the treadmill performance of the drinking-water players it was evaluated all the individuals and also was created the sub groups of Higher Run Time (HRT, n=8) and the others (WRT, n=7). Blood samples were collected before and immediately post-exercise and assayed for markers of tissue integrity (enzymes CK, AST and ALT), antioxidants (TAP and uric acid), oxidants (MDA) and anaerobiosis (lactate). It was used repeated-measures ANOVA to compare the variables in basal, pre and post-exercise; and t-test dependent to compare the delta (final-initial) values ( ) and time of treadmill run between groups, for p<0.05. Results: In all the individuals it was noted higher lactate and lower ALT levels after the exercise in mate group. The yerba mate tea group showed longer treadmill run along with higher increase of lactate and uric acid than the water group in the WRT sub group. In HRT it was observed no increase in AST and lower ALT levels in mate tea group. Conclusion: Yerba mate intake by female soccer players increased tolerance to exhaustive exercise ...

Introdução: A erva mate (Ilex Paraguariensis) é uma bebida consumida principalmente na América do Sul e contém componentes com função antioxidante e possíveis propriedades ergogênicas. Sabe-se que o exercício eleva o estresse oxidativo e a lesão muscular, portanto o consumo do chá mate poderia proporcionar efeitos benéficos. Objetivo: Avaliar o efeito do consumo agudo de chá mate nos parâmetros de estresse oxidativo e lesão muscular em jogadoras de futebol profissional que foram expostas ao exercício exaustivo. Métodos: Quinze jogadoras de futebol (22,1 ± 4,2 anos) foram avaliadas de forma randomizada consumindo 5g de chá mate solúvel (400 ml) ou 400 ml de água em estudo cruzado com 7 dias de washout. Ambas as bebidas foram fornecidas após jejum noturno e 60 minutos antes de um teste incremental de esteira até a exaustão. Todos os indivíduos ingeriram 30g de maltodextrina 30 minutos antes do início do teste. Por meio do desempenho no teste de esteira do grupo água, foram criados dois subgrupos com os indivíduos com o melhor tempo de esteira (MTE, n=8) e os outros com pior tempo de esteira (PTE, n=7). Amostras sanguíneas foram coletadas em jejum, pré e pós-exercício, sendo avaliados marcadores de lesão muscular (CK, AST and ALT), antioxidante (TAP e ácido úrico), estresse oxidativo (MDA) e anaerobiose (lactato). Foi utilizado ANOVA de medidas repetidas para comparar as variáveis basal, pré e pós exercício; e teste-t dependente para comparar os valores de delta (final-inicial) ( ) e o tempo de esteira entre os grupos chá e água. Resultados: Quando foram avaliados todos os indivíduos, notou-se maior concentração de lactato e redução das concentrações de ALT no grupo chá mate. No grupo PTE , quando houve consumo de chá mate notou-se maior tempo de esteira, lactato e ácido úrico do que o grupo que consumiu água. No grupo MTE não foi observado aumento das concentrações ...
Keywords: Erva-mate - Consumo; Stress oxidativo; Exercícios físicos; Musculos - Ferimentos e lesões; Jogadores de futebol; Muscles Wounds and injuries